Ragnar Frisch, Editor of Econometrica 1933-1954 - Bjerkholt, Olav (Econometrica, 1995)
This article relates the events that led to the establishment of the journal Econometrica, with particular emphasis on the role played by Ragnar Frisch. The origin of the name of the journal is explained. The editorial views, style, and habits of Ragnar Frisch as Editor of Econometrica is recounted. Copyright 1995 by The Econometric Society.